Physeal Injury Other Than Fracture - Peterson, Hamlet A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book documents all the ways a growth plate can be damaged, other than fracture. This damage can be inflicted by a wide variety of insults, most of which are uncommon occurrences. They all, however, have two similar characteristics: normal roentgenographs at the time of insult and premature complete or partial arrest noted weeks, months, or years later. Because of this delay, the arrest is often not suspected or recognised early. The resulting bone deformity and relative shortening usually go undetected until corrective surgery is needed. This book emphasises etiology, diagnosis, and treatment of these injuries.
Vascular Deficiency -- Disuse -- Infection -- Tumor -- Metabolic -- Neural -- Cold (frostbite) -- Heat (burn) -- Electric -- Compression -- Distraction -- Stress -- Irradiation -- Light Waves -- Sound Waves -- Shock Waves -- Atmospheric Pressure -- Oxygen -- Developmental -- Surgical -- Unknown.
Keywords: Medicine; Radiology, Medical; Orthopedics; Pediatrics; Medicine & Public Health; Orthopedics; Pediatrics; Imaging / Radiology